2020
DOI: 10.3390/ma13143125
|View full text |Cite
|
Sign up to set email alerts
|

Acid and Sulphate Attacks on a Rubberized Engineered Cementitious Composite Containing Graphene Oxide

Abstract: The objective of this research was to determine the durability of an engineered cementitious composite (ECC) incorporating crumb rubber (CR) and graphene oxide (GO) with respect to resistance to acid and sulphate attacks. To obtain the mix designs used for this study, response surface methodology (RSM) was utilized, which yielded the composition of 13 mixes containing two variables (crumb rubber and graphene oxide). The crumb rubber had a percentage range of 0–10%, whereas the graphene oxide was tested in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 58 publications
0
18
1
Order By: Relevance
“…The presence of rubber improves the resistance to sulphate attack with resistance coefficient factor of more than 100%. However, this result does not agree with the findings of (Sabapathy et al, 2020) who reported that CR above 5% in rubberized GO modified ECC has insignificant effect on sulphate attack. In a research to assess the durability of 5 years aged lightweight concrete containing rubber aggregate was conducted by Nadine et al (Asroun et al, 2017).…”
Section: Sulfate Resistencecontrasting
confidence: 99%
“…The presence of rubber improves the resistance to sulphate attack with resistance coefficient factor of more than 100%. However, this result does not agree with the findings of (Sabapathy et al, 2020) who reported that CR above 5% in rubberized GO modified ECC has insignificant effect on sulphate attack. In a research to assess the durability of 5 years aged lightweight concrete containing rubber aggregate was conducted by Nadine et al (Asroun et al, 2017).…”
Section: Sulfate Resistencecontrasting
confidence: 99%
“…A lightweight concrete mix was prepared in this research by the lightweight clay expansion as a coarse aggregate and furnace bottom ash (FBA) as a fine aggregate [120]. Results showed that the overall noise reduction was 32.50 dB in the replacement of the entire FBA with recycled rubber aggregates, which a reduction substantially above 15.50 dB was already achieved by a control concrete mix made without rubber [19,[121][122][123]. The surface of recycled rubber aggregates has been adjusted with a simple procedure for the pretreatment of cement slurry.…”
Section: Cellular Concretementioning
confidence: 97%
“…Several factors affect the concrete thermal conductivity [55]. For instance, the type of aggregate [56,57], the properties of cementitious materials [58][59][60][61][62][63][64][65][66], moisture content [67,68], design buildup [69][70][71][72][73][74], temperature [75,76], concrete density [12,[77][78][79][80], etc. The measurement of concrete thermal conduction is divided into steady-state and transient methods [81].…”
Section: Thermal Conductivitymentioning
confidence: 99%